Construcción de una escala transcultural de comportamiento actitudinal hacia el retardo mental de acuerdo a la teoría de faceta de Guttman - Jordan, John E.; Adis-Castro, Gonzalo; Zúniga, Evenor (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A 5-facet, 6 level (or 6 subscale) instrument derived from Guttman’s facet theory, the Attitude-Behavior Scale: Mental Retardation (ABS-MR), was evolved to assess attitude-behaviors toward the mentally retarded. Following Guttman, attitude was defined as a “delimited totality of behavior with respect to something.” Each of the 6 ABS-MR subscales were regarded as such a “delimited totality,” i.e., attitude was regarded as a kind of behavior.